Feasibility of Calcium Alginate Microcapsules of Oral Sustained Release Suspensions of Propranolol Hydrochloride Using Ion Exchange Resinates: Microcapsules of sustained release propranolol suspensions - Suresh N; Satish KV; Ashok Kumar BS; Kiran AS; Narayana Swamy N; Sheshadri Shaker D (Iranian Journal of Pharmaceutical Sciences, 2011)
An oral suspension could a suitable dosage form for the geriatric patients. The calcium alginate coated ion exchange resinate of propranolol hydrochloride were prepared using Amberlite IR-120 by solvent evaporation. Microcapsules of propranolol hydrochloride resinate were prepared by solvent evaporation technique, the suspensions were prepared by using deionised water as the vehicle. Methyl cellulose and Tween 80 were used as suspending agents in four different concentrations: 0.5, 1, 1.5 and 2%. The suspensions were evaluated for physical stability, redispersibilty and in vitro release patterns. Microcapsules of propranolol hydrochloride corresponding to drug polymer ratios of 1:1.0, 1:1.5, 1:2.0, 1:2.5 and 1:3.0 were evaluated for physical stability, percentage yield, particle size, and in vitro drug release profile. The drug loading capacity of ion exchange resine was found to be 41% (w/v). The suspensions were prepared with 1.5% Tween 80 had good physical stability and redispersibilty and in vitro release patterns, and were also suitable for sustained release formulation. Therefore, calcium alginate coated propranolol hydrochloride formulation as oral sustained suspension is an effective system, which can be suitable dosage form for geriatric use.